Sea cucumber derived sulfated sterols alter glucose metabolism by promoting gluconeogenesis and reducing glycogenesis in healthy mice - Shanyun Yu; Teng Wang; Yingcai Zhao; Xiaoyue Li; Changhu Xue; Yuming Wang; Tiantian Zhang (Food Science and Human Wellness)
Sea cucumber derived sulfated sterols significantly ameliorated insulin resistance and decreased lipid accumulation compared to plant sterols. Interestingly, our recent study found that intervention with sea cucumber sulfated sterols could significantly increase blood glucose levels of healthy mice in the presence of glucose, while cholesterol sulfate, as one of sulfated sterols, did not have the same effect. However, the exact mechanism of sulfated sterols on glucose metabolism is still unknown. In the present study, we investigated the potential mechanism by which sulfated sterols influenced blood glucose homeostasis in healthy mice. Results showed that intervention with sea cucumber sulfated sterols did not affect the levels of hormones related to glucose metabolism, while led to a significant decrease in the synthesis of liver glycogen and muscle glycogen. Besides, the expression of proteins associated with the promotion of gluconeogenesis dramatically increased in the mice intervened with sea cucumber sulfated sterols. These findings suggested that sea cucumber sulfated sterols might change blood glucose metabolism in healthy mice by reducing glycogenesis and promoting gluconeogenesis.